Malignant phyllodes tumor of the breast with short-term multiple recurrences and systemic distant metastasis: a case report and literature review - Zhang, Min; Zhou, Lisha; Gao, Xudong; Zhao, Mengfan; Ye, Rupei; Liang, Bin; Wu, Bin (Frontiers in Oncology, 2025)
Malignant phyllodes tumor (MPT) of the breast is a rare fibroepithelial neoplasm that is often misdiagnosed as a benign tumor or fibromatosis. It is characterized by rapid growth and a high tendency for recurrence, though distant metastasis is relatively uncommon. This case report presents a 61-year-old female patient with a breast mass that was initially suspected to be a fibroadenoma based on core needle biopsy. Consequently, she underwent lumpectomy, and postoperative pathology indicated a tendency towards desmoid-type fibromatosis. However, the tumor recurred rapidly 29 days later, prompting a subsequent total mastectomy. The final diagnosis confirmed malignant phyllodes tumor. Forty days later, during radiotherapy, the tumor recurred again with concurrent systemic distant metastasis, and the patient was subsequently initiated on systemic therapy. By analyzing the diagnostic and treatment process as well as pathological features, this report highlights the importance of early definitive diagnosis, surgical margins, adjuvant therapy, and systemic treatment in improving the prognosis of breast MPT.